2011
DOI: 10.1051/ebr:2012002
|View full text |Cite
|
Sign up to set email alerts
|

A review of the environmental safety of the Cry1Ac protein

Abstract: 1 Event refers to a single transformation event: the incorporation of a transgene into a plant genome. A single transformation event can be crossed into multiple lines.2 Tomato Event 5345 expressing Cry1Ac was deregulated by USDA APHIS but never received registration as a pesticide with the USEPA and was not commercialized anywhere in the world. It will not be considered elsewhere in this paper. 3 This includes approvals for lines generated through breeding and transformation with additional transgenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Although field-level research into non-target effects such as the present study can provide information about the ecology of GM fields, there is a considerable body of literature [ 2 , 10 , 16 18 , 21 , 95 ] that argues that such research is not necessary to perform regulatory risk assessment for GM crops. The present research supports that position in finding no unexpected adverse effects on NTA communities, a finding that was anticipated from lower tier NTA experiments conducted with higher concentrations of Bt proteins in controlled laboratory conditions [ 96 , 97 ]. Assessments for GM crops that contain insect resistance traits could be expected to require field studies only when the results from lower tier hazard testing suggest the potential for adverse effects [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although field-level research into non-target effects such as the present study can provide information about the ecology of GM fields, there is a considerable body of literature [ 2 , 10 , 16 18 , 21 , 95 ] that argues that such research is not necessary to perform regulatory risk assessment for GM crops. The present research supports that position in finding no unexpected adverse effects on NTA communities, a finding that was anticipated from lower tier NTA experiments conducted with higher concentrations of Bt proteins in controlled laboratory conditions [ 96 , 97 ]. Assessments for GM crops that contain insect resistance traits could be expected to require field studies only when the results from lower tier hazard testing suggest the potential for adverse effects [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies, reviews and meta-analyses have assessed the impacts of Bt cotton and maize on non-target organisms, in particular non-target arthropods (NTAs) [17, 25, 29–32, 52–58]. Limited work has examined the impact of Bt eggplants producing coleopteran-active Cry3Bb [59,60], but to our knowledge this is the first report of a field study that assessed the impact of Bt eggplants expressing Cry1Ac on NTAs and other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have been raised that long term and extensive use of Bt crops could directly or indirectly affect biodiversity and beneficial non-target organisms, particularly arthropods [2728]. Therefore, assessment of the environmental consequences of transgenic crops is an important prerequisite to their commercialization [29–32]. Risk of exposure to non-target arthropods (NTAs) by a Bt protein can be through direct feeding on plant tissues or consuming arthropods that have fed on plant tissues [23,31,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have detected Cry proteins in aphid samples, including those that cannot be explained by contamination, have reported very low amounts of Bt protein in the aphids 36 . There is, however, no validated evidence that Cry1Ac has any activity in arthropods outside the order of Lepidoptera, as demonstrated from the many studies on the non-target effects of Cry1Ac-expressing Bt cotton or purified Cry1Ac protein 10 52 . While information on Cry1C in the published literature is scarce, recent studies revealed no effects of this protein on the ladybird beetle Propylea japonica (Coleoptera: Coccinellidae) 53 and the green lacewing Chrysoperla sinica (Neuroptera: Chrysopidae) 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results contribute to the body of knowledge on Cry1 proteins from Bt that are expressed in commercialized Bt crops for control of lepidoteran pests (Cry1Ab/Cry1F for maize and Cry1Ac for cotton). Currently, there is no validated evidence that those proteins cause direct toxic effects to arthropods outside the target order of Lepidoptera 8 10 52 56 57 .…”
Section: Discussionmentioning
confidence: 99%